2017
DOI: 10.1073/pnas.1609348114
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Xpp1 is a switch between primary and secondary fungal metabolism

Abstract: Fungi can produce a wide range of chemical compounds via secondary metabolism. These compounds are of major interest because of their (potential) application in medicine and biotechnology and as a potential source for new therapeutic agents and drug leads. However, under laboratory conditions, most secondary metabolism genes remain silent. This circumstance is an obstacle for the production of known metabolites and the discovery of new secondary metabolites. In this study, we describe the dual role of the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 62 publications
0
60
0
Order By: Relevance
“…During host colonization, fungal plant pathogens elicit an array of symptoms in the plant, many of which stem not only from the modulation of the plant immune system but also from reprogramming of host development processes (Oliver and Ipcho, 2004;Horbach et al, 2011;Cordovez et al, 2017). Indeed, while studies surveying single trait interactions have highlighted key processes and pathways critical to pathogenesis of fungi in plants (Derntl et al, 2017;Fang et al, 2017), genomic and transcriptomic studies suggest fungi have a complex and elaborate infection program (Brown et al, 2017;Chowdhury et al, 2017). Comparative transcriptomics during fungal colonization have revealed that infection programs vary by fungal lifestyle, suggesting that induced pathways diverge within biotrophic, hemibiotrophic, and/or necrotrophic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…During host colonization, fungal plant pathogens elicit an array of symptoms in the plant, many of which stem not only from the modulation of the plant immune system but also from reprogramming of host development processes (Oliver and Ipcho, 2004;Horbach et al, 2011;Cordovez et al, 2017). Indeed, while studies surveying single trait interactions have highlighted key processes and pathways critical to pathogenesis of fungi in plants (Derntl et al, 2017;Fang et al, 2017), genomic and transcriptomic studies suggest fungi have a complex and elaborate infection program (Brown et al, 2017;Chowdhury et al, 2017). Comparative transcriptomics during fungal colonization have revealed that infection programs vary by fungal lifestyle, suggesting that induced pathways diverge within biotrophic, hemibiotrophic, and/or necrotrophic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The RNASeq data used in this study was generated in a previous study by Derntl et al [23]. Therein the wildtype like T. reesei strain QM6a Δtmus53 strain [34] cultivated in Mandels-Andreotti medium [35] containing 1% carboxy methyl cellulose as carbon source.…”
Section: Extraction Of Rna and Sequencingmentioning
confidence: 99%
“…After 48 h of solid-state incubation at 30°C, the RNA was isolated using the RNeasy Plant Mini Kit (Quiagen) and libraries were prepared using a TruSeq Stranded mRNA Sample Prep Kit including poly (A) enrichment (Illumina). The libraries were sequenced on a NextSeq500 instrument (Illumina) with paired-end 75 nt long reads [23].…”
Section: Extraction Of Rna and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to primary metabolites, SMs are often considered as non-essential for fungal growth, development or reproduction. However, SMs can be crucial for long-term survival in competitive fungal niches (Fox and Howlett, 2008; Ponts, 2015; Derntl et al, 2017). SMs produced by plant pathogenic fungi are of particular interest as they may contribute to virulence, leading to crop losses and threatening food security (Ponts, 2015; Pusztahelyi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%